FAKTOR TRUST, TRANSPARENCY DAN ACCOUNTABILITY (Studi pada Aplikasi Layanan Digital Badan Penyelenggara Jaminan Sosial Tenaga Kerja) - Mahira Husna, - (2020)
The result of this study are expected to develop the quality of service and quality of information provided to information users so that will increase the user's satisfaction and trust for the government according to existing policy. This study uses a modified model of the DeLoneMcLean and UTAUT model to measure the success of the information systems and user acceptance of information system. There are six construct variables of performance expectancy, effort expectancy, facilitating conditions, information quality, willingness to adopt and three additional variables are trust, transparency and accountability. SEM PLS is used as the research method. From the result of this study, it was found that effort expectancy, facilitating conditions, trust, transparency accountability, system quality positively affect willingness to adopt. Meanwhile, performance expectancy and information quality negatively affect willingness to adopt. This model is expected to be able to measure the affects in using e-government, so this can be used as material of evaluation to develop information system for the citizens in the future. Keyword : DeloneMclean, UTAUT, SEM PLS